Investigating the thermal stability of the chemical vapour deposited zirconium carbide layers - Biira, Saphina; Thabethe, T.T.; Hlatshwayo, T.T.; Bissett, H.; Ntsoane, T.; Malherbe, J.B. (Journal of Alloys and Compounds, 2020)
The effect of thermal treatment on zirconium carbide (ZrC) layers deposited by chemical vapour deposition process was investigated using X-ray diffraction (XRD), Raman spectroscopy, nanoindention and scanning electron microscopy (SEM). The ZrC layers deposited at 1400 C (composed of 96% ZrC and 4% C) were annealed at 1500, 1600, 1700 and 1800 C for 2 h under high vacuum of 2.6 10 7 mbar. After annealing, the lattice constant and the average crystallite sizes were found to increase whereas the lattice strain and dislocation density decreased. The preferred orientation of the as-deposited layers was (220); it changed to (200) when annealed at 1500 C and 1600 C. At annealing temperature of 1700 C and 1800 C, the preferred orientation was (220) just like for the as-deposited ZrC layers. From Raman spectroscopy analysis, the ID/IG ratio reduced from 0.694 to 0.414 with annealing temperature indicating an improvement in crystallinity level and a decrease in the defects in the carbon material in the ZrC layers. The hardness of the layers was found to decrease slightly with annealing temperature from 26.4 ± 0.6 GPa to 21.3 ± 0.5 GPa. Some voids initially present in the as-deposited ZrC layers closed up and particles increased in size with annealing temperature.
Keywords: Annealing temperature; Chemical vapour deposition; ZrC layers; Microstructural properties; Surface morphology